2013
DOI: 10.1371/journal.pone.0083752
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Dynamical Insights into the Membrane-Bound α-Synuclein

Abstract: Membrane-induced disorder-to-helix transition of α-synuclein, a presynaptic protein, has been implicated in a number of important neuronal functions as well as in the etiology of Parkinson’s disease. In order to obtain structural insights of membrane-bound α-synuclein at the residue-specific resolution, we took advantage of the fact that the protein is devoid of tryptophan and incorporated single tryptophan at various residue positions along the sequence. These tryptophans were used as site-specific markers to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
66
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(76 citation statements)
references
References 64 publications
9
66
0
1
Order By: Relevance
“…39,7071 WT α-syn is devoid of Trp residues, enabling single-Trp incorporation as local fluorescent probes. It is well-established that Trp membrane penetration can be monitored via fluorescence quenching by the heavy-atom bromine incorporated at specific positions along the lipid hydrocarbon chain.…”
Section: Resultsmentioning
confidence: 99%
“…39,7071 WT α-syn is devoid of Trp residues, enabling single-Trp incorporation as local fluorescent probes. It is well-established that Trp membrane penetration can be monitored via fluorescence quenching by the heavy-atom bromine incorporated at specific positions along the lipid hydrocarbon chain.…”
Section: Resultsmentioning
confidence: 99%
“…The REES effect is, therefore, a unique probe for proteins with a high degree of molecular flexibility resulting in an ensemble of solvent environments around the Trp probe. For proteins, such an ensemble may arise from a broad equilibrium of conformational states, such as in molten globule intermediates of highly flexible or dynamic proteins [14,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, multifunctional properties of α-syn are predicted by its structure that has been attributed to this protein [33]. The structure flexibility property of α-syn allows it to accept a wide range of conformations depending on binding partners and environment [34,35]. Because of its abundant presence at presynaptic terminals, chaperone function of α-syn is the key cellular function, which controls the exocytosis through trafficking and organizing the synaptic vesicle pool.…”
Section: α-Syn a Major Mediator In Pd Pathogenesismentioning
confidence: 99%
“…Many studies have clearly demonstrated that baicalein protected 6-hydroxydopamine (6-OHDA), 1-methyl-4-phenylpyridinium (MPP+), glutamate, amyloid-β (Aβ), hydrogen peroxide (H 2 O 2 ), 1-methyl-4-phenyl-1,2,3,6tetrahydropyridine (MPTP), and methamphetamine-induced neurotoxicity in animal models and cell lines [27][28][29][30][31][32][33]. Earlier, some authors clearly reviewed the anticancer, anti-inflammatory, cardioprotective properties, ocular disorders, and mitochondrial function [34][35][36][37]. Li et al [38] briefed the therapeutic properties of baicalein against PD.…”
Section: Baicalein As a Potential Molecule Of Natural Origin To Targementioning
confidence: 99%